The Perceived Impact of Employee Motivation on the Productivity of Millennials (Generation Y) in the Workplace - Mofokeng, Mamodupi (The IIE, 2020)
Employee motivation is positive work behaviour and willingness towards carrying out organisational objectives. It is a concept that has been considered ever since the discovery of Maslow’s Hierarchy of Needs in the 1950s. Firms tend to profit from employee motivation, the main advantage being improved productivity (include a statistic here). Even though there is previous literature regarding employee motivation, there is less known about millennial employee motivation in particular. The purpose of this study was to access the perceived impact of employee motivation on the productivity of millennials or Generation Y employees in the work place. Qualitative questionnaires were given out to five participants, all of whom are employees. It was found that employee motivation does not impact a millennial employee’s productivity. There are other factors that need to be considered such as – passion and genuine love for the work at hand. Thus, the results suggest that employee motivation does not influence millennial productivity within the workplace.
Keywords: Millennials; Generation Y; Employee motivation; Perceptions; Workplace productivity